Social Media Usage in Nonprofit Wrestling Organizations: A Cross-Platform Analysis. Issue 1 (2nd January 2016) - Giannoulakis, Chrysostomos; Burch, Lauren; Brgoch, Shea
ABSTRACT: This case study examined the social media use of USA Wrestling during the 2014 National Collegiate Athletic Association Division I Wrestling Championships in the United States. We performed a cross-platform content analysis of the organization's Facebook, Twitter, YouTube, and Instagram accounts during the 3 days of the event using a relationship-marketing framework. In addition, we conducted qualitative interviews with employees involved with the National Governing Body's social media implementation. Results indicated predominant use of Twitter and YouTube, with 375 posts occurring during the 3-day event as compared with 8 posts on Facebook and Instagram, cumulatively. Such an approach contradicted interviewees' responses on the popularity of Facebook. Overall, the organization placed particular emphasis on information-sharing posts across the 4 platforms pertaining to wrestling and athletes during the event. We discuss the theoretical and practical implications for wrestling-related organizations.